Demographic, occupational, and societal features associated with burnout among medical oncology staff members: Cross‐sectional results of a Cancer Center in Beijing, China. Issue 12 (15th November 2019) - Chen, Zhishui; Leng, Jiahua; Pang, Ying; He, Yi; Heng, Fanxiu; Tang, Lili
Abstract: Background: There is a growing recognition that medical staff members are exposed to job and life stressors that increase the risk of burnout. This study aimed to investigate the potential stressors among medical staff members working at a Cancer Center in Beijing and to explore the demographic, occupational, and societal features associated with burnout. Methods: This was a cross‐sectional study. The Maslach Burnout Inventory (MBI) survey was distributed to all medical staff members, along with an anonymous questionnaire to collect general information about demographic, occupational, and societal characteristics. The data were analyzed using T test, ANOVA, and multivariable linear regression. Results: A total of 1096 of 1208 (91%) medical staff members completed the questionnaires, including 285 (26%) doctors and 572 (52%) nurses. The scores for emotional exhaustion (EE), depersonalization (DP), and personal accomplishment (PA) were 14.51 ± 9.78, 5.78 ± 5.59, and 35.07 ± 10.43, respectively. Domicile, being a nurse, working overtime, and low self‐rated QoL were predictors of EE; Domicile, being a researcher, low self‐rated health, low self‐rated QoL, and bad colleague relationships were predictors of DP; Age, being a doctor or a nurse, low self‐rated health, and low self‐rated interpersonal relationships were predictors of low PA. Conclusion: Compared with the other occupations, doctors and nurses are more likely to experience burnout. Additionally, cultivating a better work environment, promoting the health and quality of life of staff, and improving rapport with colleagues may help to prevent burnout.